Gothic Expression in Contemporary American Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses issues of Gothic expression in contemporary American literature. It deals primarily with the interpretation of Gothic works, their meaning and significance, the period in which the works were written, and covering multiple types of Gothic expression psychological, postmodern, feminist, and Southern Gothic. The methods align well with the research questions, ensuring that the study provides in-depth literary analysis rather than superficial observations. However, the Eco-Gothic subgenre is not fully represented among the primary texts, which could have strengthened the analysis of environmental themes.